Evaluation of the antibacterial activities of skin mucus from Asian swamp eel (Monopterusalbus) - Mahmood, Syed; Ayah Rebhi, Hilles; Ridzwan, Hashim (NISCAIR PUBLICATIONS, 2019)
The water covers more than two-thirds of the Earth's surface, and almost 90 % of the world's species are found in the water environment. Therefore, it is necessary to explore drugs from marine and freshwater organisms. The skin of marine and freshwater animals are covered with a mucus layer, which acts as a biochemical and mechanical barrier for their skin. This study aimed to investigate the potential antibacterial activity of Asian swamp eel(Monopterusalbus) skin mucus. Aqueous and methanol extracts were prepared to detect the antimicrobial activities with different extract concentrations from 0.49 to 1000 μg/mL against various pathogens, i.e. Staphylococcus aureus and Escherichia coli. The antibacterial activities were determined by measuring the diameter of inhibition zone, minimal inhibitory concentration, minimal bactericidal concentration, inhibition percentage, and survival percentage. The results showed inhibition in bacterial growth, which was treated with both methanol extract and the aqueous extract. However, methanol extract has significantly higher antibacterial activities than the aqueous one. At 100 µl/disc, the inhibition zone of methanol extract against E. coli was10.7 ± 0.17 mm while 9.9 ± 0.06 mm against S. aureus. The percentage of bacterial inhibition for eel skin mucus (ESM) methanol extract against E. coli showed higher inhibition (72.46 %) than against S. aureus(68.45 %) at 1000 µl/mL. ESM aqueous extract showed the highest bacterial survival rate against S. aureus at 7.81 µg/mL, which was 71.11 %, whereas the methanol extract was 58.25 %. The results were statistically significant, with p < 0.001. In conclusion, the current study revealed that eel skin mucus might be considered as a promising source for antibacterial activities.